2016
DOI: 10.1128/jvi.01640-15
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Molecular Mechanism Driving Duplication of the HIV-1 PTAP Late Domain

Abstract: HIV-1 uses cellular machinery to bud from infected cells. This cellular machinery is comprised of several multiprotein complexes known as endosomal sorting complexes required for transport (ESCRTs). A conserved late domain motif, Pro-Thr-AlaPro (PTAP), located in the p6 region of Gag (p6 Gag ), plays a central role in ESCRT recruitment to the site of virus budding. Previous studies have demonstrated that PTAP duplications are selected in HIV-1-infected patients during antiretroviral therapy; however, the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 77 publications
1
29
1
Order By: Relevance
“…Therefore, this domain appears to be necessary for viral budding. Although one report shows that PTAP duplication only increases HIV-1 replication in the presence of a PI (26), others and we observed increased viral growth when HIV-1 contained a PTAP duplication (25). Although deletion of the PTAP motif has not been identified in clinical strains so far, artificial deletion or mutation of this PTAP motif severely abrogates release of HIV-1 from infected cells (11, 32, 33).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Therefore, this domain appears to be necessary for viral budding. Although one report shows that PTAP duplication only increases HIV-1 replication in the presence of a PI (26), others and we observed increased viral growth when HIV-1 contained a PTAP duplication (25). Although deletion of the PTAP motif has not been identified in clinical strains so far, artificial deletion or mutation of this PTAP motif severely abrogates release of HIV-1 from infected cells (11, 32, 33).…”
Section: Discussioncontrasting
confidence: 61%
“…We also included two HIV-1C strains with a PTAP duplication (PT02 and PT03) as it has been shown to increase the viral fitness and affect the drug sensitivity (Fig. 5a) (25, 26). Then, these sequences were cloned into the genome of a reference virus (NL4-3, HIV-1B wild type) replacing its gag-pol sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively low number of failures did not allow us to observe any association with Gag p6 genotype and viral failure. A recent study reported that PTAP-duplications enhance the resistance to several protease inhibitors (PIs) [Martins et al, 2015]. However, in our drug sensitivity assay including all available PIs, no difference was observed in EC 50 fold change between either PTAPduplicated HIV-1B or HIV-1C viruses (Supplementary File S1).…”
Section: Discussionmentioning
confidence: 68%
“…First, we altered the N-terminus as the suspected primary binding site for IDE [48] by duplication of the N-terminal PTAP-motif, a mutation that is frequently observed in clinical HIV-isolates as it augments virus maturation under antiviral treatment [49,50]. To mimic these natural N-terminal alterations, we generated a p6 mutant containing two PTAPPA domains (further referred to as 2x, Fig 8B) and tested its stability by in vitro degradation assays using S10 and rIDE combined with synthetic or virally-produced substrates of the 2x mutant version.…”
Section: Resultsmentioning
confidence: 99%